Assessment of wild mint from Tunceli as source of bioactive compounds, and its antioxidant Activity - Turkoglu, S. (C M B Assoc, 2015)
The types of wild mint (Mentha spicata L.) were sampled from different geographical regions in Tunceli (Turkey) in order to find out their vitamin, mineral, phenolic contents and their antioxidant properties. The total phenol varied from 77.7 +/- 0.242 to 52.34 +/- 0.351 mg of GAEs/g of dry mint. The highest radical effect of scavenging was observed in Mazgirt parting of the ways 7.5 km with 6.17 +/- 0.245 mg/mL. The highest reducing power and metal chelating were observed in the mint from Cicekli parting of the ways 6.5 km Demirkapi. Among the various macronutrients which were estimated in the plant samples, potassium was presented in the highest quantity followed by calcium and phosphate. Although rutin and resveratrol were not determined in any samples, kaempferol and catechin levels were found out in almost all samples. The concentrations of vitamin A ranged between 42,14 +/- 5.70 and 13.61 +/- 3.00 (mg/kg dry weight). These results show that plants of mint are quite rich in phenolic compounds, and these have been appeared to have antioxidant activity, which agrees with this work, since the extract showed a higher content of phenolic compounds and higher antioxidant activity and mint may be considered as a natural alternative source for food, pharmacology and medicine sectors.
Keywords: Mentha spicata; antioxidant activity; phenolic content; elemental composition; vitamin